Trans-oesophageal Echocardiographic Appraisal of Left Atrial Appendage Clot in Severe Mitral Stenosis. - Simkhada, Rabindra; KC, Man Bahadur; Bhatt, Yadav Deo; Maskey, Arun; Malla, Rabi; Sharma, Deewakar; Rajbhandari, Rajeeb; Limba, Yuba Raj; Kansakar, Subodh; Baidhya, Sajan Gopal; Shama, Ranjit; Nepal, Himanshu Prasad; et al. (Nepalese Heart Journal, 2014)
Background and Aims Left atrial appendage clot is a common complication of mitral stenosis. The management of patient differs significantly if there is presence of clot. Various factors had been studied as a risk factor for clot formation. We aim to assess the prevalence of left atrial appendage clot by trans-oesophageal echocardiography in patients of severe mitral stenosis planned for percutaneous transvenous mitral commissurotomy and analyze the factors responsible for it. Methods: An oservational prevalence study was conducted among 100 patients of severe mitral stenosis who were undergoing transoesophageal echocardiography before percutaneous transvenous mitral commissurotomy and prevalence of left atrial appendage clot were recorded. Data were entered in the SPSS and factors responsible for clot formation were analyzed. Results: Out of 100 enrolled patients, 69 (69%) were female. Mean age of presentation was 37.4±13.70 years. Mean age of female was 38.11±13.13 years and male was 35.80±14.98 years. Mean mitral valve area was 0.87±0.12 cm2 and mean left atrial size was 4.79±0.60 cm. Atrial Fibrillation was present in 32 (32%) patients. Transoesophageal echocardiography revealed left atrial appendage clot in 28 (28%). Gender showed no correlation with presence of clot (p=0.06). Increasing age (p=0.002), presence of Atrial Fibrillation (p=0.005) and larger left atrial size (p<0.01) showed significant positive correlation with left atrial appendage clot formation. Conclusion: Left atrial appendage clot was common finding in severe mitral stenosis patients. Patients with advanced age, presence of atrial fibrillation and larger left atrial size were more likely to have clot formation. Nepalese Heart Journal | Volume 10 | No.1 | November 2013| Pages 27-29 DOI: http://dx.doi.org/10.3126/njh.v10i1.9744